1999
DOI: 10.1111/1467-6427.00104
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and religion in training, practice and personal development

Abstract: In the midst of a revitalized interest in spirituality and religion in Western societies, there has been reported a resurgence of activity regarding spirituality and religion in the mental health professions, including marriage and family therapy (MFT). Little is known, however, about the beliefs, behaviours, and training experiences of MFT graduate students. Therefore it is important to examine the training (education and supervision) needs in this area. For this initial study, a sample of US MFT graduate stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 26 publications
(38 reference statements)
7
75
0
Order By: Relevance
“…The conclusion from most research in this area highlights the fact that despite the importance of religion/spirituality in most clients' lives, practitioners are not given adequate training to prepare them to deal with issues arising in these realms (Delaney, et al, 2007;Shafranske & Malony, 1990). Surveys have shown that professionals reported addressing religious and spiritual issues in their clinical practice yet these issues were rarely or never addressed in the course of their training (Delaney, et al, 2007;Lannert, 1991;Prest, Russel, & D'Souza, 1999;Shafranske & Malony, 1990). …”
Section: Including Spirituality In the Training Processmentioning
confidence: 99%
“…The conclusion from most research in this area highlights the fact that despite the importance of religion/spirituality in most clients' lives, practitioners are not given adequate training to prepare them to deal with issues arising in these realms (Delaney, et al, 2007;Shafranske & Malony, 1990). Surveys have shown that professionals reported addressing religious and spiritual issues in their clinical practice yet these issues were rarely or never addressed in the course of their training (Delaney, et al, 2007;Lannert, 1991;Prest, Russel, & D'Souza, 1999;Shafranske & Malony, 1990). …”
Section: Including Spirituality In the Training Processmentioning
confidence: 99%
“…The acknowledgement that clinicians ought to address spirituality with clients (Griffith & Griffith, 2002;Richards & Bergin, 1997), therefore, has naturally extended to the need for supervisors to discuss this issue with therapists-in-training. Recent authors have argued that spirituality is a key construct for MFT supervisors and supervisees to consider (Carlson & Erickson, 2001;Coffey, 2002;Miller, 1999;Miller et al, 2006Miller et al, , 2004Prest, Russel, & D'Souza 1999;Stander, Piercy, Mackinnon, & Helmeke, 1994). This study examined spirituality as a construct in supervision, based on the supervisee's perspective.…”
Section: Spirituality In Marriage and Family Therapy Trainingmentioning
confidence: 99%
“…Several authors (Frame, 2001;Harris, 1998;Prest & Keller, 1993;Prest et al, 1999) discussed how MFT training programs tend to overlook spiritual issues, emphasizing that unless trainees attend programs that espouse spiritual beliefs, spirituality is rarely addressed. Harris (1998) challenged supervisors and therapists to seek spiritual explanations for the basic tenets of MFT theories.…”
Section: Spirituality In Marriage and Family Therapy Trainingmentioning
confidence: 99%
“…While research and writing on spirituality in the field of marriage and family therapy (MFT) is still in its infancy, in the past decade a growing body of literature on this topic has emerged (Anderson, & Worthen, 1997;Becvar, 1997;Carlson, Kirkpatrick, Hecker, & Killmer, 2002;Giblin, 1996;Haug, 1998a;Moules, 2000;Prest, Russel, & D'Souza, 1999;Walsh, 1999;Walsh & Pryce, 2003). However, very little empirical research that explores the role of spirituality in the MFT field has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…These studies explored the attitudes and beliefs of clinical members of the American Association for Marriage and Family Therapy (AAMFT) and MFT students related to the importance they place on the role of spirituality in their own lives, their clinical work, and the training and education of MFTs (Carlson et al, 2002;Prest et al, 1999). Findings in each of these studies indicated that over 90% of AAMFT clinical members and MFT students considered themselves to be spiritual persons, and over 85% reported that they believed there is a relationship between spiritual health and mental health.…”
Section: Introductionmentioning
confidence: 99%